Zakat and Income Inequality in Indonesia: Panel Data Analysis in 34 Provinces - Nurrizka Puji Lestari; Ilmiawan Auwalin (Universitas Airlangga, 2022)
ABSTRAK Tujuan utama dari makalah ini untuk menguji secara empiris pengaruh zakat, Produk Domestik Regional Bruto (PDRB) perkapita, Upah Minimum Regional/Provinsi (UMP), dan inflasi terhadap tingkat gini rasio di 34 provinsi di Indonesia selama tahun 2018-2020. Temuan penelitian ini menunjukkan bahwa distribusi zakat yang diproksikan dengan Indeks Kesejahteraan BAZNAS serta tingkat inflasi secara statistik tidak berpengaruh signifikan terhadap tingkat ketimpangan pendapatan di Indonesia. Sementara itu, tingkat PDRB perkapita dan UMP memiliki arah hubungan negatif dan berpengaruh signifikan secara statistik terhadap tingkat ketimpangan pendapatan di Indonesia. Penelitian ini memberikan rekomendasi kepada pengelola zakat untuk menciptakan dan mengembangkan program zakat yang mampu memberdayakan perekonomian mustahik sehingga mampu mengurangi tingkat kesenjangan pendapatan dalam masyarakat. Selain itu, seluruh pemangku kepentingan (stakeholders) harus bersinergi dalam upaya meningkatkan realisasi pengumpulan dana zakat di lembaga dengan melalui peningkatan literasi dan kesadaran masyarakat guna mengoptimalisasikan peran zakat dalam peningkatan kesejahteraan masyarakat. Kata kunci: Indeks Kesejahteraan BAZNAS, Ketimpangan Pendapatan, Makroekonomi, Zakat. ABSTRACT The main objective of this paper was to empirically examine the effect of zakat, Gross Regional Domestic Product (GRDP) percapita, Regional/Provincial Minimum Wage, and inflation on the gini ratio in 34 provinces in Indonesia during 2018-2020. The findings of this study indicate that the distribution of zakat, which is proxied by the BAZNAS Welfare Index, and the inflation rate has no statistically significant effect on the level of income inequality in Indonesia. Meanwhile, GRDP per capita and Regional/Provincial Minimum Wage levels have a negative and statistically significant relationship to the level of income inequality in Indonesia. In order to lessen the degree of income inequality in society, this study offers recommendations to zakat managers on how to design and develop zakat programs that can strengthen the mustahik's economy. In addition, all stakeholders must work together in an effort to increase the realization of zakat fund collection in institutions by increasing literacy and public awareness in order to maximize the contribution of zakat to raising the welfare of mankind. Keywords: Baznas Welfare Index, Income Inequality, Macroeconomics, Zakat. REFERENCES Abdelbaki, D. H. H. (2013). The impact of zakat on poverty and income inequality in Bahrain. Review of Integrative Business & Economics Reseacrh, 2(1), 133–154. Afandi, A., Rantung, V. P., & Marashdeh, H. (2017). Determinants of income inequality. Economic Journal of Emerging Markets, 9(2), 159–171. DOI: 10.20885/ejem.vol9.iss2.art5 Afandi, M. F. M., Zubairi, M. I. N., Hashim, M. J., & Khamis, M. R. (2021). The role of zakat in reducing income inequality among muslim society in Selangor. Global Business and Management Research: An International Journal, 13(4), 1–12. Ahmad, M. U., & Mahmood, A. (2009). Zakat fund-concept and perspective. International Journal of Monetary Economics and Finance, 2(3/4), 197–205. DOI: 10.1504/IJMEF.2009.029058 Alamanda, A. (2021). The effect of economic growth on income inequality: panel data analysis from fifty countries. Info Artha, 5(1), 1–10. DOI: 10.31092/jia.v5i1.1176 Anshari, M., Azhar, Z., & Ariusni. (2019). Analisis pengaruh pendidikan, upah minimum provinsi dan belanja modal terhadap ketimpangan pendapatan di seluruh provinsi di indonesia. Jurnal Ecogen, 1(3), 494–502. DOI: 10.24036/jmpe.v1i3.4990 Asongu, S., & Odhiambo, N. (2019). Inequality and the economic participation of women in sub-Saharan Africa: An empirical investigation. African Journal of Economic and Management Studies. DOI: 10.1108/AJEMS-01-2019-0016 Badan Pusat Statistik. (2021a). Gini rasio. Retrieved from https://sirusa.bps.go.id/sirusa/index.php/indikator/999 Badan Pusat Statistik. (2021b). PDB/PDRB per kapita. Subdit Rujukan Statistik, Badan Pusat Statistik. https://sirusa.bps.go.id/sirusa/index.php/indikator/74 Badan Pusat Statistik. (2021c). Tingkat ketimpangan pengeluaran penduduk Indonesia Maret 2021 (Issue 54/07/Th. XXIV). Badan Pusat Statistik. (2021). Tingkat ketimpangan pengeluaran penduduk Indonesia September 2020 (Issue 17/02/Th. XXIV). Bucevska, V. (2019). Determinants of income inequality in EU candidate countries: A panel analysis. Economic Themes, 57(4), 397–413. DOI: 10.2478/ethemes-2019-0023 Caraka, R. E. (2017). Spatial data panel (Pertama). WADE Group. Carter, V. J., & Howard, M. W. (2020). Income inequality. In Encyclopedia Britannica. Retrieved from https://www.britannica.com/topic/income-inequality Charities Aid Foundation. (2021). CAF world giving index 2021 (Issue June). Chun, N., & Khor, N. (2010). Minimum wages and changing wage inequality in Indonesia (196). Asian Development Bank Darsono, S. N. A. C., Raihana, M., Jati, H. F., & Pachmi, A. (2019). The impact of productive zakat on the income inequality of mustahiq in Yogyakarta. Journal of Economics Research and Social Sciences, 3(1), 56–71. DOI: 10.18196/jerss.030107 Deyshappriya, N. P. R. (2017). Impact of macroeconomic factors on income inequality and income distribution in asian countries (No. 696). Asian Development Bank Institute Fadila, N. R. (2019). Correlation of zakat distribution with Gini index: Maximizing the potential of zakat for equitable income distribution in Indonesia. Airlangga International Journal of Islamic Economics and Finance, 2(1), 54-65. DOI: 10.20473/aijief.v2i1.21994 Fitri, C. D., Maulana, H., & Safitri, A. (2018). Analisis pengaruh penyaluran zakat terhadap ketimpangan pendapatan dan tingkat kemiskinan di Provinsi Aceh periode 2007-2017. Ekobis: Jurnal Ekonomi Dan Bisnis Syariah, 2(2), 45-54. Gujarati, D. N., & Porter, D. C. (2015). Panel data regression models. In Basic Econometrics (Edisi Kelima, pp. 591–605). Douglas Reiner. Ha, N. M., Le, N. D., & Trung-Kien, P. (2019). The impact of urbanization on income inequality: a study in Vietnam. Journal Risk Financial Management, 12(3), 1–14. DOI: 10.3390/jrfm12030146 Hafidhuddin, D. (2002). Zakat dalam perekonomian modern (Pertama). Gema Insani. Halimatussa’idah, H., & Prasetyo, A. (2021). Bencana alam dan BI rate terhadap penghimpunan dana ZIS dengan inflasi sebagai variabel intervening pada BAZNAS Indonesia. Jurnal Ekonomi Syariah Teori Dan Terapan, 8(1), 32–42. DOI: 10.20473/vol8iss20211pp32-42 Hendri, D. (2014). Kriminalitas: sebuah sisi gelap dari ketimpangan distribusi pendapatan. Jurnal Ekonomi Dan Kebijakan Publik, 5(2), 239–252. Iqbal, I. (2020). Zakat: macroeconomic and microeconomic demands. International Journal of Economics, Business and Management Research, 4(3), 1-9. Kalsum, U. (2018). Distribusi pendapatan dan kekayaan dalam ekonomi Islam. Li Falah Jurnal Studi Ekonomi Dan Bisnis Islam, 3(1), 41–59. Kamaludin Yusup, D., Sobana, D. H., & Fachrurazy, F. (2021). The effectiveness of zakat distribution at the national zakat agency. Al-’Adalah, 18(1), 55–76. DOI: 10.24042/adalah.v18i1.9912 Karim, A. A. (2015). Ekonomi makro Islam (Ketiga). PT Rajagrafindo Persada. Kementerian Agama RI. (2013). Panduan zakat praktis. Kemenag RI. Kousar, R., Rais, S. I., Mansoor, A., Zaman, K., Tahir, S., Shah, H., & Ejaz, S. (2019). The impact of foreign remittances and financial development on poverty and income inequality in Pakistan : evidence from ARDL-Bounds testing approach. The Journal of Asian Finance, Economics, and Business, 6(1), 71–81. DOI: 10.13106/jafeb.2019.vol6.no1.71 Kurniawan, A. W., & Puspitaningtyas, Z. (2016). Metode penelitian kuantitatif (Pertama). Pandiva Buku. Lahjouji, H., & Rouggani, K. (2016). Zakat and distribution of wealth on Islamic economy: Case of Morocco. International Journal of Islamic Economics and Finance Studies, 2(3), 151–160. DOI: 10.12816/0036637 Lin, C., & Yun, M. S. (2016). The effects of the minimum wage on earnings inequality: evidence from China (No. 9715). DOI: 10.1108/S0147-912120160000044012 Logaritma, S. (2021). Produk domestik regional bruto provinsi-provinsi di Indonesia menurut lapangan usaha 2016-2020. Badan Pusat Statistik. Mahfuzha, A., Rizki, C. Z., Sapha, D., Fitriyani, F., Jamal, A., & Weri, W. (2019). Is zakat important in reducing poverty?. Social Science, Education and Humanities Research, 292, 558–562. DOI: 10.2991/agc-18.2019.83 Mankiw, N. G. (2010). Principles of macroeconomics (Keenam). South-Western Cengage Learning. Monnin, P. (2014). Inflation and income inequality in developed economies. SSRN Electronic Journal. Munandar, T. A., & Wardoyo, R. (2015). Fuzzy-Klassen model for development disparities analysis based on gross regional domestic product sector of a region. International Journal of Computer Applications, 123(7), 17–22. DOI: 10.5120/ijca2015905389 Nabila, N., & Herianingrum, S. (2020). Pengaruh zakat sebagai salah satu produk filantropi terhadap tingkat inflasi di Indonesia periode 2015-2017. Jurnal Ekonomi Syariah Teori Dan Terapan, 7(3), 420–430. DOI: 10.20473/vol7iss20203pp420-430 OECD. (2021). Income inequality (indicator). DOI: 10.1787/459aa7f1-en Pusat Kajian Strategis Badan Amil Zakat Nasional. (2019). Indeks kesejahteraan BAZNAS. BAZNAS. Pusat Kajian Strategis Badan Amil Zakat Nasional. (2021). Hasil pengkuran kaji dampak zakat 2020. BAZNAS. Pusat Kajian Strategis BAZNAS. (2021). Outlook zakat Indonesia 2022. BAZNAS. Rahmadi, S., & Parmadi. (2019). Pengaruh ketimpangan pendapatan dan kemiskinan terhadap pertumbuhan ekonomi antar pulau di Indonesia. Jurnal Paradigma Ekonomika, 14(2), 55–66. DOI: 10.22437/paradigma.v14i2.6948 Ramzai, J. (2020). Clearly explained: gini coefficient and lorenz curve. Medium. Retrieved from https://towardsdatascience.com/clearly-explained-gini-coefficient-and-lorenz-curve-fe6f5dcdc07 Ratnasari, D., & Rosyidi, S. (2019). Dampak kesenjangan antara penerimaan dan penyaluran dana ZIS terhadap program-program LAZNAS Al-Azhar. Jurnal Ekonomi Syariah Teori Dan Terapan, 6(3), 489–509. DOI: 10.20473/vol6iss20193pp489-509 Saputri, R. G. C. (2017). Pengaruh produktivitas sektoral dan laju PDRB terhadap tingkat ketimpangan pendapatan di Jawa Tengah pada tahun 2006 – 2015. Jurnal REP (Riset Ekonomi Pembangunan), 2(2), 103–112. DOI: 10.31002/rep.v2i2.226 Saripudin, U., Djamil, F., & Rodoni, A. (2020). The zakat, infaq, and alms farmer economic empowerment model. Library Philosophy and Practice (e-Journal). 3566. Sarwono, J. (2006). Metode penelitian kuantitatif dan kualitatif (Pertama). Penerbit Graha Ilmu. Senadjki, A., Nachef, T., & Rusli, N. (2015). The impact of zakat on income inequality and poverty in Malaysia: a panel data analysis. Market Forces College of Management Sciences, x(1). Setiawan, B. (2015). Teknik hitung manual analisis regresi linear berganda dua variabel bebas. DOI: 10.31227/osf.io/gd73a Siami-Namini, S., & Hudson, D. (2019). Inflation and income inequality in developed and developing countries. Journal of Economic Studies, 46(3), 611–632. DOI: 10.1108/JES-02-2018-0045 Siyoto, S., & Sodik, A. (2015). Dasar metodologi penelitian (Pertama). Literasi Media Publishing. Srihardianti, M., Mustafid, & Prahutama, A. (2016). Metode regresi data panel untuk peramalan konsumsi energi di Indonesia. Jurnal Gaussian, 5(3), 475–485. DOI: 10.14710/j.gauss.v5i3.14703 Sukwika, T. (2018). Peran pembangunan infrastruktur terhadap ketimpangan ekonomi antarwilayah di Indonesia. Jurnal Wilayah dan Lingkungan, 6(2), 115–130. DOI: 10.14710/jwl.6.2.115-130 Sungkar, S. N., Nazamuddin, & Nasir, M. (2015). Pengaruh upah minimum terhadap ketimpangan pendapatan di Indonesia. Jurnal Ilmu Ekonomi, 3(2), 40–53. Suryani, K. G., & Woyanti, N. (2021). The effect of economic growth, HDI, district/city minimum wage and unemployment on inequity of income distribution in province of D.I Yogyakarta (2010-2018). Media Ekonomi Dan Manajemen, 36(2), 170–180. DOI: 10.24856/mem.v36i2.1990 Syafiq, A. (2016). Zakat ibadah sosial untuk meningkatkan ketaqwaan dan kesejahteraan sosial. ZISWAF: Jurnal Zakat Dan Wakaf, 2(2), 380–400. DOI: 10.21043/ziswaf.v2i2.1558 Syahrum, & Salim. (2016). Metodologi penelitian kuantitatif (R. Ananda (ed.)). Citapustaka Media. Trimaya, A. (2014). Pemberlakuan upah minimum dalam sistem pengupahan nasional untuk meningkatkan kesejahteraan tenaga kerja. Aspirasi: Jurnal Masalah-Masalah Sosial, 5(1), 11–20. DOI: 10.46807/aspirasi.v5i1.448 Untari, R., Priyarsono, D. S., & Novianti, T. (2019). Impact of Information and Communication Technology (ICT) infrastructure on economic growth and income inequality in Indonesia. International Journal of Scientific Research in Science, Engineering and Technology, 6(1), 109–116. DOI: 10.32628/ijsrset196130 World Population Review. (2021). Muslim population by country 2021. https://worldpopulationreview.com/country-rankings/muslim-population-by-country Yuliani, R., Rahman, Y. A., Nuraini, D., & Khotimah, K. (2021). Determinants of income inequality in Yogyakarta Province. International Conference on Strategic Issues of Economics, Business and, Education (ICoSIEBE 2020), 301–305. DOI: 10.2991/aebmr.k.210220.053